Innovative polypropylene based blends by in situ polymerization of a polyimide dispersed phase by reactive extrusion. (21st July 2022) - Dubois, Charlotte; Marestin, Catherine; Cassagnau, Philippe; Delage, Karim; Alcouffe, Pierre; Garois, Nicolas; Bounor-Legaré, Véronique
Abstract: Polypropylene/polyimide (PP/PI) blends were synthesized by reactive extrusion with the in situ polymerization of the polyimide phase in presence of maleic anhydride grafted polypropylene (PP-g-MA) as a compatibilizer. Blends were reactively processed in a twin-screw extruder at 200 °C, with the PI content varying from 10 to 40 wt%. Examination of morphology by scanning electron microscopy (SEM) depicted a fine sub-micrometer dispersion of the polyimide phase ranging from 170 to 250 nm in diameter, for all PI concentrations. The advantage of the in situ approach compared to the more classical dispersion process was clearly demonstrated. The in situ synthesized PI phase was characterized by NMR and FTIR after separation by Soxhlet selective extraction. Differential scanning calorimetry (DSC) analysis of the blends showed no modifications of PP crystallinity with the addition of PI. Rheological behaviors showed a significant impact of the polyimide phase on the storage modulus with the appearance of a secondary storage modulus plateau at low frequencies. Thermogravimetric analyses evidenced an improvement of the thermal stability of the blends, with an increase of the decomposition temperature up to 35 °C depending on the polyimide content. Mechanical properties were also improved due to the high mechanical strength of the polyimide phase, with an increase in Young's modulus up to +35 % for the highest polyimide content. Graphical abstract: Image 1 Highlights: Polyimide was in situ synthetized in PP phase. A fine sub-micrometer dispersion of the polyimide phase ranging from 170 to 250 nm was obtained. Increase in Young's modulus up to +35% for the highest polyimide content.